Post-quantum cryptography 4th international workshop, PQCrypto 2011, Taipei, Taiwan, November 29-December 2, 2011: proceedings - Yang, Bo-Yin (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 4th International Workshop on Post-Quantum Cryptography, PQCrypto 2011, held in Taipei, Taiwan, in November/December 2011. The 18 revised full papers presented were carefully reviewed and selected from 38 submissions. The papers cover a wide range of topics in the field of post-quantum public key cryptosystems such as cryptosystems that have the potential to resist possible future quantum computers, classical and quantum attacks, and security models for the post-quantum era.